A selective and cost-effective method for the reductive deuteration of activated alkenes. Issue 28 (12th July 2017) - Li, Hengzhao; Zhang, Bin; Dong, Yanhong; Liu, Ting; Zhang, Yuntong; Nie, Haiyu; Yang, Ruoyan; Ma, Xiaodong; Ling, Yun; An, Jie
Graphical abstract: Highlights: A new reductive deuteration reaction of activated alkenes has been developed. High levels of D incorporation and excellent yields have been achieved across a broad range of substrate. This method uses stable, commercially-available reagents and is operationally-simple. Abstract: A new single electron transfer reaction for the reductive deuteration of activated alkenes has been developed for the selective synthesis of α, β -dideuterio compounds. A cheap, stable and commercially-available sodium dispersion with high specific surface area is employed as the electron donor to replace the traditionally used sodium/liquid ammonium system. Deuterium source is provided by EtOD- d 1 . Excellent yields and deuterium incorporations were obtained across a broad range of activated alkenes with good functional group tolerance. This method provided a cheap, efficient and operationally-simple method for the synthesis of deuterium labeled compounds.